Comparison of efficacy of Lignocaine 1.5 mg/kg & Dexmedetomidine 1 μg/kg in attenuating the hemodynamic pressure response to laryngoscopy & intubation - Pingle, Sujit; Sharma, Pallavi; Dhumane, Pradeep; Raipure, Amrusha; Sharma, Abhay (International Journal of Medical Research and Review, 2019)
Background: Dexmedetomidine attenuates the hemodynamic stress response tolaryngoscopy and intubation more effectively compared with Lignocaine without any deleterious effects. To study the efficacy of Lignocaine 1.5 mg/kg & Dexmedetomidine 1 μg/kg in attenuating the hemodynamic pressure response to laryngoscopy & intubation. Material and Methods: A total of 100 American Society of Anesthesiologists (ASA) physical status I and II patients aged between 18 and 50 years undergoing elective surgery were enrolled in the study. Patients posted for elective surgery were randomly selected and divided into two groups. Group L = 50 Patients had given 1.5mg/kg Lignocaine; Group D = 50 Patients had given 1µg / kg Dexmedetomidin. Results: In Dexmedetomidine group, HR, SBP, DBP and MAP showed significant decrease throughout the study period, as compared to Lignocaine group. The statistical analysis shows that, in Dexmedetomidine group, HR, SBP, DBP and MAP showed significant decrease throughout the study period, as compared to Lignocaine group. Conclusion: Newer agents like Dexmedetomidine, a centrally acting alpha-2 agonist suppresses reflex sympathetic stimulation caused by laryngoscopy & intubation more effectively than Lignocaine. Thus, it is concluded that Dexmeditoedine is a better drug compared to Lignocaine in attenuating pressure response to laryngoscopy & intubation.